FAKTOR-FAKTOR YANG MEMPENGARUHI PAY OUT POLICY PADA PERUSAHAAN PUBLIK THAILAND - Savira, Ditha Hena; Hamid, Agustini (Academic Research Centre Services, 2018)
We investigate the relationship between Free Cash Flow, Life Cycle and Dividend pay out policy in the Thailand Capital Market. Using panel data regression, we find life cycle and profitability negatively affect the pay out policy. While free cash flow, leverage, firm size, GDP and inflation do not have any impact on pay out policy. In line with DeAngelo, dividends tend to follow the pattern of the company?s life cycle. Companies that are in the mature stage are more likely to pay dividends because at this stage the company has a large amount of profits and low investment opportunities. While companies that are still in the growth stage (growth) are more likely to not pay dividends because at this stage the company has a high investment opportunities, nevertheless they have limited funding. As found in many emerging countries, the Public Companies in Thailand are mostly in growth stage, thus no wonder that profits are used to finance the company?s internal needs